(untitled) (Palíndromo, 2018)
This article presents the process of creation of visual artist Juliana Crispe (Florianópolis, 1982). The propositions of Juliana point out directions to be thought with main basis in the concept of me-mory, and in how the memories of its life make possible the creative subsidy of its artistic objects. The text presents a biographical character, of the relationship lived between author and artist, and sometimes insinuates a personal and affective tone. The way of writing adopted is purposeful, since it presents one of the triggers for Juliana’s work: it becomes a constitutive part of the artistic process. The thread of the article is the story of Irenaeus Funes, a character created by Borges, a figure suitable for weaving the analogies and convergences of two memory fables. Some postulates by authors such as Henri Bergson, Jacques Derrida and Didi-Huberman, make it possible to broaden the concepts approached and enter the world of the artist’s resignification, giving a reflection on how the works emerge and begin to transmit, in a poetic way, all their heterogeneity and anachronism.